2012
DOI: 10.1371/journal.pone.0031359
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Murine Intranasal Dosing Efficiency Using Luminescent Francisella tularensis: Effect of Instillation Volume and Form of Anesthesia

Abstract: Intranasal instillation is a widely used procedure for pneumonic delivery of drugs, vaccine candidates, or infectious agents into the respiratory tract of research mice. However, there is a paucity of published literature describing the efficiency of this delivery technique. In this report we have used the murine model of tularemia, with Francisella tularensis live vaccine strain (FTLVS) infection, to evaluate the efficiency of pneumonic delivery via intranasal dosing performed either with differing instillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 52 publications
1
73
1
Order By: Relevance
“…Less invasive methods include intranasal administration, whereby bacterial dose is administered in droplets through the nostrils followed by aspiration by the animal (52), or aerosol administration, that can be performed in unrestrained animals (53). However, the exact dose that reaches the lower respiratory tract in both methods is uncontrolled and animals frequently develop upper respiratory tract infections (52) or infections other than pneumonia (53). One method to control dose delivery with aerosolization is to immediately sacrifice a few (sentinel) animals after aerosolization for quantitative colony counts performed on bronchoalveolar lavage fluid or lung tissue lysates (53).…”
Section: Types Of Pneumonia Modelsmentioning
confidence: 99%
“…Less invasive methods include intranasal administration, whereby bacterial dose is administered in droplets through the nostrils followed by aspiration by the animal (52), or aerosol administration, that can be performed in unrestrained animals (53). However, the exact dose that reaches the lower respiratory tract in both methods is uncontrolled and animals frequently develop upper respiratory tract infections (52) or infections other than pneumonia (53). One method to control dose delivery with aerosolization is to immediately sacrifice a few (sentinel) animals after aerosolization for quantitative colony counts performed on bronchoalveolar lavage fluid or lung tissue lysates (53).…”
Section: Types Of Pneumonia Modelsmentioning
confidence: 99%
“…While relatively simple, caveats such as instillation volume and type of anesthesia used can impact the efficiency of instillation into the LRT via intranasal inoculation [3][4][5] . Specifically, Miller et al have shown that intranasal instillation of Francisella tularensis in volumes less than 50 µl did not result in instillation of the bacteria into the LRT 6 . They further observed better LRT instillation when using inhaled isoflurane as opposed to injected ketamine/xylazine for anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been used by a number of investigators in different settings to deliver materials of interest to mouse lungs, including inhalation, intranasal instillation, intratracheal instillation, and intratracheal intubation [1][2][3][4] . The latter procedure has not been routinely used because it is considered rather difficult to perform.…”
Section: Introductionmentioning
confidence: 99%